Analysis on the design of steel wire wound extrusion containers for hot extrusion process. (July 2017) - Liu, Changyong; Zhang, Renji; Yan, Yongnian; Lao, Changshi
Extrusion container is the most important tooling for steel hot extrusion process. Conventional design using large castings and forgings is very difficult to execute due to high cost and risk. Steel wire wound containers have many advantages over conventional designs. However, conventional wire wound containers are developed for use at room temperature which are not applicable to steel hot extrusion process. In this article, the impacts of preheating on the design of steel wire wound containers are discussed in detail. A finite element model was established to examine the preheating temperature distribution, and a 1:10 scaled extrusion container was manufactured to verify the effectiveness of the finite element model. Based on the finite element model–computed temperature field, thermal stress analysis was performed. The thermal impacts on the stress of extrusion container and steel wire were obtained. Results showed that insufficient stability of internal cylinder and greatly enhanced steel wire stress may lead to the failure of extrusion container. To solve the problems, an improved design was put forward by increasing the stability factor of internal cylinder, reducing the prestress factor and lowering the allowable stress of steel wire. Results showed that the improved design can meet the requirements and counteract the thermal impacts.